Experience of local targeted administration of chondroprotective drugs into the zone of pathological changes in the labrum of the acetabulum in coxarthrosis - N. V. Sazonova; L. V. Maltseva; S. N. Luneva; E. L. Matveeva; A. G. Gasanova; M. A. Kovinka (Лечащий Врач, 2021)
There has been developed a local directional symptomatic slow-acting drug (SYSADOA) injection method into the zone of pathologically changed articular lip (of cartyloid cavity). The drug was administered once 1 every 3 days, with 3-5 injections required for the treatment of one joint. The treatment course was 9-15 days. After the course had been completed, all patients were improved the structure of the articular lip, and, along with the suppression of pain syndrome, the cysts disappeared or significantly decreased in size, the density of the fibrous cartilage ring decreased. In patients with a cartilaginous lip cyst in the long-term period, a more pronounced positive dynamics was determined than in the presence of cysts in the femoral head region. After treatment, blood serum and urine collagen degradation rates decreased and metabolic changes developed characterizing the balance shift between resorption and bone formation towards the predominance of the latter. The developed method for treating early coxarthrosis with local administration of the drug with chondroprotective effect made it possible to reduce pain syndrome, the duration of NSAID intake, and reduce the duration of conservative treatment.